Pembangunan sistem pemasaran menggunakan konsep 'Adaptive Marketing' - Yussof, Soffri (2007)
Marketing is one of the important element in business process. The Internet trends nowadays let marketing activities to be done globally. Marketing is use to market products or services at the perfect target market and at the right time. The target market is the people which are an important entity that plays their roles in increasing a business organization to be more profitable. On top of that, business organization trying to develop better products and services and market them by an effective approach for consumer satisfaction. An approach that is effective to consumer will attracts more consumer simultaneously develop an organization to participate in the global market. Realizing this factor, this project is to develop a system call The Development of Marketing System based on Adaptive Marketing Concept. Prototype Methodology was used in developing this system and Macromedia Dreamweaver MX is the software to develop the system and MYSQL is the database. The future project is to assist Keharsons Sdn Bhd in managing an effective and efficient marketing activities as well as supporting customer purchasing decisions.